The Influence Of Liquidity, Leverage and Firm Size on Financial Distress at First Media Tbk. Period 2013-2022 - Maulana, M. Iqbal; Rusnendar, Elan; Musadat, Irfan Achmad (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2025)
Financial distress can occur in any company, whether small or large. Additionally, the COVID-19 pandemic has caused economic instability in Indonesia, impacting the telecommunications sector and resulting in many companies experiencing financial distress, including PT. First Media Tbk, which has faced a decline in performance for more than five consecutive years. This study aims to determine the extent of the influence of liquidity, leverage, and firm size on the financial distress of PT. First Media Tbk. during the period 2013-2022. The indicators used in this study are the current ratio for liquidity, the debt to asset ratio for leverage, the natural logarithm for firm size, and the Z" score for financial distress. The method used in this research is descriptive and verification with a quantitative approach. The population and sample used in the study consist of 10 financial statements from PT. First Media Tbk. The results of the t-test (partial) show that leverage has a value of 5.947, firm size has a value of 2.246, and liquidity has a value of 1.611, indicating that leverage and firm size have a partial effect on the financial distress of PT. First Media Tbk. during the period 2013-2022, while liquidity does not have a partial effect on the financial distress of PT. First Media Tbk. during the same period. The results of the F-test (simultaneous) show a value of 20.463, indicating that liquidity, leverage, and firm size simultaneously affect the financial distress of PT. First Media Tbk.